2017
DOI: 10.1167/tvst.6.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Biological Involvement of MicroRNAs in Proliferative Vitreoretinopathy

Abstract: Even with a high surgical success rate for retinal detachment and proliferative vitreoretinopathy (PVR) supported by the robust improvement in vitrectomy surgery and its related devices, certain questions still remain for the pathogenesis and treatment of PVR. One of the important biological events in PVR is epithelial–mesenchymal transition (EMT) of the retinal pigment epithelial (RPE) cells. MicroRNAs are noncoding, small, single-strand RNAs that posttranscriptionally regulate gene expression and have essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Recently, in a model of OIR, in mice, we demonstrated that BK/B2R is involved in the pathological retinal neovascularization and that this effect correlated with upregulation of FGF-2 in retinal vessels [ 22 ]. A limited number of studies suggest the existence of a functional link between the two systems in several inflammatory/angiogenic disorders [ 28 , 29 , 30 ]. Although FGF-2 can trigger neovessel formation per se, the major finding of this study concerns the BK ability to transactivate FGFR-1 signaling in endothelial cells, as evidenced by its phosphorylation and translocation from the plasma membrane to cytosol, and, in turn, by the phosphorylation of second messengers downstream to FGFR-1, as FRSα, ERK1/2, and STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a model of OIR, in mice, we demonstrated that BK/B2R is involved in the pathological retinal neovascularization and that this effect correlated with upregulation of FGF-2 in retinal vessels [ 22 ]. A limited number of studies suggest the existence of a functional link between the two systems in several inflammatory/angiogenic disorders [ 28 , 29 , 30 ]. Although FGF-2 can trigger neovessel formation per se, the major finding of this study concerns the BK ability to transactivate FGFR-1 signaling in endothelial cells, as evidenced by its phosphorylation and translocation from the plasma membrane to cytosol, and, in turn, by the phosphorylation of second messengers downstream to FGFR-1, as FRSα, ERK1/2, and STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies suggests that the angiogenic response induced by BK/B2R system could be mediated by the upregulation of proangiogenic factors [ 25 ]. Although evidence for the direct activation of the FGF-2 or VEGF pathway by BK in vivo is not yet available, there is indirect evidence suggesting a functional link between the two systems in several inflammatory diseases, including vasoactive responses [ 17 , 18 , 19 , 20 , 26 ]. Notably, in this study, in the model of OIR, we observed that endothelial cells from retinal vessels express FGF-2 and VEGF, and that fasitibant reduced the expression of both growth factors, also marginally affecting HIF-1α expression.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-2 stimulates VEGF secretion from vascular smooth muscle, endothelial and Müller cells and synergizes with VEGF in promoting the proliferation of retinal microvascular endothelial cells and pericytes [ 15 , 16 ]. Furthermore, FGF-2 and VEGF levels, as the KKS components, are significantly increased in vitreous from experimental models of retinal diseases [ 17 ], as well as at sites of chronic inflammation [ 18 ], where both growth factors and BK appear to be the key metabolic mediators of inflammatory responses, including vasoactive responses [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several cell types are associated with the PVR pathogenesis, including retinal pigment epithelial (RPE) cells, fibroblasts, glial cells, and inflammatory cells. RPE cells are the largest cellular component in epiretinal membranes, and, importantly, they undergo dedifferentiation process -epithelial-mesenchymal transition (EMT) -in which they acquire a mesenchymal phenotype (Kaneko & Terasaki, 2017;Yang et al, 2016). This process is the main contributor to PVR progression and involves a number of molecular pathways affecting cell proliferation and migration.…”
Section: Proliferative Vitreoretinopathymentioning
confidence: 99%